Predictive modelling of thermal comfort using physiological sensing - Chaudhuri, Tanaya (2019)
A thermally comfortable building indoor environment is imperative for human health and work productivity. Although the major energy consumption in a tropical building is attributed to its Air-Conditioning and Mechanical Ventilation (ACMV) cooling systems, yet complaints of thermal dissatisfaction is prevalent among occupants. Prediction of the occupant’s thermal comfort can be instrumental in bridging this gap by utilizing the predicted thermal state (Cool-Discomfort/Comfort/Warm-Discomfort) as a control criterion for the ACMV system. However, the existing thermal comfort prediction methods rely primarily on environmental information. We envision that a possibly simpler approach would be a direct investigation of the human physiological parameters, since the bodily responses are direct consequences of surrounding thermal ambiance.